DIFFERENT TYPES OF WRITING IN TEACHING AND LEARNING PROCESS (Proceedings of International Educators Conference, 2023)
Writing as a skill is very important in learning English. It helps students to assimilate letters and sounds of the English language, its vocabulary and grammar. Writing is one of the main language skills and learning it is very important in teaching English. Nowadays the issue of increasing the efficiency of teaching English which is one of the main disciplines in the school, college, lyceums, institutes, universities’ curriculums is one of the urgent issues in methods of teaching English as a foreign language. Teaching writing should be started from beginning level. Most school textbooks are focused on teaching writing separately without integration of other skills. The significance of the work can be proved that we tried to analyze types of writing skills in teaching and learning process.